Transforming conflict as an approach to solving international conflicts: a conceptual approach - Messali, Leila; Hamadouche, Riad (Journal of Human Sciences, 2022)
As is well known, during the last years of the last century, the world witnessed changes, affecting all fields, including the field of international relations, which has become the scene of many interactions between all the actors, which made it characterized by many phenomena, the most important of which is the spread of the phenomenon of internal conflicts. Therefore, we will try through this research paper to address one of the most important mechanisms that have been relied upon to resolve the conflict. It is the mechanism for transforming conflict, which is considered one of the most effective mechanisms as it aims to convert relations between the conflicting parties from hostile relations to friendly cooperative relations. Therefore, we ask the following question: How does the process of conflict transformation contribute to solving international conflicts in a manner that achieves security and lasting and positive peace?